Inequality and the crisis: the distributional impact of tax increases and welfare and public sector pay cuts - Callan, Tim; Nolan, Brian; Keane, Claire; Walsh, John R. (Economic & Social Studies, 2010)
The economic crisis impacts directly on the distribution of income via unemployment and private sector wages, but the way policy responds in seeking to control soaring fiscal deficits is also central to its distributional consequences. Having sketched out the background in terms of inequality trends during Ireland?s boom and the channels through which the recession affects different parts of the income distribution, this paper investigates the distributional impact of the government?s policy response with respect to direct tax, social welfare and public sector pay using the SWITCH tax-benefit model. This provides empirical evidence relevant to future policy choices as efforts to reduce the fiscal deficit continue.
Policy paper presented at a symposium on ?The Crisis, Welfare State Retrenchment and Social Cohesion: Lessons from Social Science?
Keywords: Inequality; Taxation policy; Public spending; Income distribution